2008
DOI: 10.1073/pnas.0805462105
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic osteosarcoma induced by inactivation of Rb and p53 in the osteoblast lineage

Abstract: Mutation of the RB-1 and p53 tumor suppressors is associated with the development of human osteosarcoma. With the goal of generating a mouse model of this disease, we used conditional and transgenic mouse strains to inactivate Rb and/or p53 specifically in osteoblast precursors. The resulting Rb;p53 double mutant (DKO) animals are viable but develop early onset osteosarcomas with complete penetrance. These tumors display many of the characteristics of human osteosarcomas, including being highly metastatic. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
275
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(288 citation statements)
references
References 25 publications
10
275
1
2
Order By: Relevance
“…Recent reports describing novel OS models indicate that OS originates from lineage-committed immature osteoblasts or MSCs (Berman et al, 2008;Walkley et al, 2008). Our model suggested that OS can originate from both types of cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Recent reports describing novel OS models indicate that OS originates from lineage-committed immature osteoblasts or MSCs (Berman et al, 2008;Walkley et al, 2008). Our model suggested that OS can originate from both types of cells.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, novel mouse OS models were developed through targeted deletion of p53 and Rb in osterixexpressing cells (Berman et al, 2008;Walkley et al, 2008). INK4a/ARF exerts effects on both the Rb and p53 pathways (Collado et al, 2007).…”
Section: Ink4a-myc Bmscs Form Os In Syngeneic Micementioning
confidence: 99%
“…(15) However, the tumor that arises in this model system has been noted to express more primitive lineage markers than preosteoblasts. (16) Although these markers may be acquired in the transformation process, it also has been suggested that a rare precursor cell that expresses markers of both mesenchymal stem cells and preosteoblasts may be the cell of origin. (16) Targeted disruption of p53 and Rb in the mesenchymal cells of the murine limb bud also produces sarcomas.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…(16) Although these markers may be acquired in the transformation process, it also has been suggested that a rare precursor cell that expresses markers of both mesenchymal stem cells and preosteoblasts may be the cell of origin. (16) Targeted disruption of p53 and Rb in the mesenchymal cells of the murine limb bud also produces sarcomas. (17) A separate line of evidence comes from the observation that serially passaged murine mesenchymal stem cells will undergo rare spontaneous transformation resulting in an osteosarcoma-like tumor, suggesting that these cells are the cell of origin.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…(31) Indeed, genomic profiling of human OS has not revealed recurrent genetic events, (1) although mouse genetic models implicating the p53 and pRb genes have been developed recently. (32,33) OS-specific oncogenic changes therefore may not exist, and OS initiation and progression instead may be driven by alterations that also occur in other cancers (eg, p53, pRb, and Met). (1) Met is one of the most commonly altered tyrosine kinases in human cancer, (4) and Met overexpression is a common feature of OS and the more prevalent soft tissue sarcomas (STSs).…”
Section: Discussionmentioning
confidence: 99%